2021
DOI: 10.1177/2050640620949714
|View full text |Cite
|
Sign up to set email alerts
|

Optimal diagnostic accuracy of quantitative faecal immunochemical test positivity thresholds for colorectal cancer detection in primary health care: A community‐based cohort study

Abstract: Background Optimizing colonoscopy resources is challenging, and information regarding performing diagnostic quantitative faecal immunochemical test (FIT) in daily clinical practice in primary health care is still limited. This study aimed to assess the sensitivity, specificity, positive predictive value and negative predictive value of varying FIT positivity thresholds on colorectal cancer (CRC) detection in primary health care. Methods A retrospective cohort study of 38,675 asymptomatic and symptomatic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
2
23
2
Order By: Relevance
“…Finally, other large service evaluation studies 10 , 14 have now demonstrated similar results to those from the present data set, and the recently published NICE FIT study 15 adds high-volume multicentre research data to this consensus. No test is perfect, but there is now a high volume of data to demonstrate that FIT adds significant value to symptoms alone in aiding the decision to refer.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, other large service evaluation studies 10 , 14 have now demonstrated similar results to those from the present data set, and the recently published NICE FIT study 15 adds high-volume multicentre research data to this consensus. No test is perfect, but there is now a high volume of data to demonstrate that FIT adds significant value to symptoms alone in aiding the decision to refer.…”
Section: Discussionsupporting
confidence: 85%
“…The significant risk of CRC associated with a high FIT demonstrates the value of FIT for stratifying patients that need urgent investigation wherever diagnostic capacity is constrained, as well as in the challenging environment brought on by COVID-19. Conversely, a negative FIT corresponds with a 0.3% risk of CRC in this cohort which is consistent with previous service evaluation as well as emerging data from multicentre research studies [7,11]. FIT appears safe for "rule out" and our data confirm its utility across all groups including IDA.…”
Section: Discussionsupporting
confidence: 90%
“…The lower f-Hb values were chosen because 2 mg/g is the LoD, 7 mg/g is the LoQ, <10 mg/g was used as the value that was communicated to the GP as a robust indication that, with the exceptions noted earlier, further investigation was not generally required, as per NICE DG30 6 and <20 mg/g has been recommended as the most appropriate f-Hb value for the rather different clinical setting of asymptomatic population screening for CRC 23 and has been used in assessment of symptomatic patients in at least one other study. 24 Table 4 shows the characteristics of all the patients with a f-Hb <20 mg/g who were diagnosed with CRC, either as a result of their initial referral immediately after the f-Hb result, or subsequently identified by interrogating the available databases or linkage to the SCR.…”
Section: Resultsmentioning
confidence: 99%
“…The lower f-Hb values were chosen because 2 µg/g is the LoD, 7 µg/g is the LoQ, <10 µg/g was used as the value that was communicated to the GP as a robust indication that, with the exceptions noted earlier, further investigation was not generally required, as per NICE DG30 6 and <20 µg/g has been recommended as the most appropriate f-Hb value for the rather different clinical setting of asymptomatic population screening for CRC 23 and has been used in assessment of symptomatic patients in at least one other study. 24 …”
Section: Resultsmentioning
confidence: 99%